Molecular Mechanisms of Kaposi Sarcoma Development - Andy Karabajakian (Cancers, 2022)
Kaposi’s sarcoma (KS) is a heterogeneous angioproliferative tumor that generally arises in the skin. At least four forms of this disease have been described, with the ‘HIV’-related form being the most aggressive and can involve mucosae or visceral organs. Three quarters of KS cases occur in sub-Saharan Africa (SSA) as geographic variation is explained by the disparate prevalence of KS-associated herpes virus (KSHV), which is the underlying cause of this disease. It can infect endothelial and/or mesenchymal cells that consequently transdifferentiate to an intermediate state. KSHV establishes a latent phase in host cells in which latency proteins and various non-coding RNAs (ncRNAs) play a complex role in proliferation and angiogenesis. It also undergoes periods of sporadic lytic reactivation triggered by various biological signals in which lytic stage proteins modulate host cell signaling pathways and are key in KS progression. Complex interactions with the microenvironment with production of inflammatory cytokines with paracrine signaling is a standout feature of KS development and maintenance. KSHV impairs the immune response by various mechanisms such as the degradation of a variety of proteins involved in immune response or binding to cellular chemokines. Treatment options include classical chemotherapy, but other novel therapies are being investigated.